2019
DOI: 10.1097/sla.0000000000003209
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Patient-controlled Analgesia Versus Thoracic Epidural Analgesia After Open Liver Surgery

Abstract: Objective: We conducted a randomized, controlled, noninferiority trial to investigate if intravenous, multimodal, patient-controlled analgesia (IV-PCA) could be noninferior to multimodal thoracic epidural analgesia (TEA) in patients undergoing open liver surgery. Summary Background Data: The increasing use of minimally invasive techniques and fast track protocols have questioned the position of epidural analgesia as the optimal method of pain management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 41 publications
1
32
1
Order By: Relevance
“…Five RCTs [35][36][37][38][39] and one meta-analysis 40 compared the analgesic effect of TEA with opioid intravenous PCA. The meta-analysis that included four RCTs (n=278 patients) demonstrated that, compared with opioid intravenous PCA, TEA provided superior pain relief at rest and with movement at 12 and 24 hours after surgery, with no significant difference in hospital length of stay (LOS).…”
Section: Thoracic Epidural Analgesiamentioning
confidence: 99%
See 1 more Smart Citation
“…Five RCTs [35][36][37][38][39] and one meta-analysis 40 compared the analgesic effect of TEA with opioid intravenous PCA. The meta-analysis that included four RCTs (n=278 patients) demonstrated that, compared with opioid intravenous PCA, TEA provided superior pain relief at rest and with movement at 12 and 24 hours after surgery, with no significant difference in hospital length of stay (LOS).…”
Section: Thoracic Epidural Analgesiamentioning
confidence: 99%
“…One RCT compared TEA with ketobemidone (opioid) intravenous PCA combined with intravenous NSAIDs, while both groups received acetaminophen on a scheduled basis. 38 Another placebo-controlled RCT compared intraoperative TEA with sham epidural analgesia and intrathecal morphine (500 µg) and fentanyl (15 µg). Patients in the TEA group suffered less pain at rest and with movements, and demonstrated significantly lower opioid use.…”
Section: Thoracic Epidural Analgesiamentioning
confidence: 99%
“…16 However, epidural analgesia is a more invasive method for postoperative pain control and may cause serious complications. 16,17 Furthermore, compared with IV-PCA, additional pain reduction using epidural analgesia seemed modest in these procedures. 16 Hence, the optimal form of analgesia after abdominal surgery remains debated.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, opioid-based IV-PCA with an adjunct could provide sufficient pain relief, similar to thoracic epidural analgesia, after video-assisted thoracic surgery, leading to moderate-to-severe postoperative pain. 11 Hausken et al 17 20 demonstrated that intraoperative DEX infusion could decrease bleeding and provide a better surgical field, because of more stable hemodynamics. In addition, a meta-analysis showed that systemic administration of DEX could significantly decrease intraoperative blood loss in nasal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Patients experience mild to moderate postoperative incision site pain after thyroidectomy or parathyroidectomy, and opioid analgesics are prescribed to relieve the pain [5]. But inappropriate opioid usage patterns can increase drugrelated adverse effects,risk for dependence and abuse, and perioperative complications,morbidity [17].Several studies have demonstrated that multimodal analgesia (MMA) can effectively relieve postoperative pain and reduce the consumption of opioid analgesics following orthopedic, thoracic, and gastric surgery [18][19][20].A previous study showed that MMA protocol including use of nonopioid multimodal agents, incorporating NSAIDs, is safe,and declined in prescription of postoperative opioid analgesics for patients undergoing thyroid and parathyroid surgery [21].Additionally,administration of local anesthesia before incision can prevent central sensitization and relieve postoperative acute pain. In view of the its ability to block the branches of super cial cervical plexus including lesser occipital, greater auricular, transverse cervical,and supraclavicularnerves,BSCPB has been performed in neck surgery.…”
Section: Discussionmentioning
confidence: 99%